The moderating effect of product attributes in Vendor Managed Inventory (VMI) performance - Radzuan, Kamaruddin; Mohamed Udin, Zulkifli; Othman, Siti Norezam; Anuar, Herman Shah; Osman, Wan Nadzri (Penerbit UTM Press, 2015)
The suitability of product attributes for successful VMI program has been discussed by numerous authors and but not concluded yet.This study is to explain the moderating effects of product attributes toward VMI performance.The data was gathered from 101 of suppliers in manufacturing companies.Data analysis was conducted by employing factor analysis, reliability test, and hierarchical multiple regressions.The findings show that only level of demand visibility is the main predictor of service performance.While, replenishment decision and inventory ownership were predictor to cost performance.The innovative product moderates the relationship between level of demand visibility and VMI performance.The functional product moderates the relationship between replenishment decision and service performance; and the relationship between inventory ownership and cost performance.Suppliers in manufacturing companies should urge their customer to share demand information when engaging in VMI program.However, supplier should give less authority in replenishment decision for functional product to increase the service performance.Supplier also should have low ownership of inventory to ensure better cost saving for functional product.